Capecitabine Can Induce T Cell Apoptosis: A Potential Immunosuppressive Agent With Anti-Cancer Effect - Zhang, Sai; Wang, Zhenglu; Fan, Shunli; Liu, Tao; Yoshida, Sei; Yang, Shuang; Liu, Lei; Hou, Wen; Cao, Lei; Wang, Jianxi; Song, Zhuolun; Li, Shanni; et al. (Frontiers in Immunology, 2021)
Capecitabine (CAP) is now widely used in the comprehensive treatment of digestive system tumors. Some clinical observations have shown that CAP may have immunosuppressive effects, but there is still a lack of clear experimental verification. In this study, different doses of CAP were administered to normal mice by gavage. Our results confirmed that CAP did not cause myelosuppression in bone marrow tissue; CAP selectively reduced the proportion of T cells and the concentration of related pro-inflammatory cytokines, while it increased the concentration of anti-inflammatory cytokines. Thymidylate phosphorylase (TP) is the key enzyme for the transformation of CAP in vivo; this study confirmed that T cells express TP, but the bone marrow tissue lacks TP expression, which explains the selectivity in pharmacodynamic effects of CAP. In addition, it was confirmed that CAP can induce T cell apoptosis in vivo and in vitro. In vitro experiments showed that CAP-induced T cell apoptosis was related to TP expression, endoplasmic reticulum stress (ERS) induction, reactive oxygen species (ROS) production, and mitochondria-mediated apoptosis activation. Therefore, this study confirmed that the differential expression of TP in cells and tissues explains why CAP avoids the toxic effects of myelosuppression while inducing T cell apoptosis to exert the immunosuppressive effect. Therefore, CAP may become an immunosuppressive agent with a simultaneous anti-cancer effect, which is worthy of further studies.